BUILDING COMPETITIVE SHARED LEADERSHIP TO IMPROVE THE PERFORMANCE OF SOUTH SUMATERA PROVINCE GOVERNMENT - Ahmad Rizali; Badia Perizade; Sulastri; Agustina Hanafi (Dinasti International Journal of Education Management And Social Science, 2020)
The performance of the South Sumatra Provincial Government is reflected in the quality of innovation, program development, public services, and administrative processes related to the task and function of improving people's welfare. Performance productivity is measured by reducing poverty, increasing economic growth, and increasing local income. One of the improvements in performance is the work of middle level management in addition to the work of other levels of top management and low management. This study will answer the question of what factors can significantly to improve the performance of the government of South Sumatra Province. This paper will examine the factors of self-efficacy and affective commitment which are seen as determinants of improving the performance of the government of South Sumatra province, because it is one of the advantages of human resources and is a productive added value. However, previous studies on self-efficacy and affective commitment provide evidence that these two factors produce inconsistent research findings or gaps. Therefore empirically recommends that the effect of self-efficacy and affective commitment to improve performance requires further research to be justified. To resolve the gap of self-efficacy and affective commitment to the performance of the government of South Sumatra province, researchers adopted the theory of goal setting with the concept of competitive leadership with good organizational indicators, applying technology, sustainable work programs, and developing wider networks as a result of efficacy self and affective commitment can henceforth be used to improve organizational performance. The sample was used 108 respondents who held administrative positions with SEM LISREL 9.30 data processing. This conceptual model is expected to prove thatcompetitive shared leadership that is influenced by self-affication and affective commitment significantly improves the performance of the government of South Sumatra province.